Comparative Analysis of the Development of China and US Online Trading Platforms and Research on the Strategies of China Online Trading Platforms - Wu, Binghan (Transactions on Economics, Business and Management Research, 2024)
This paper begins by defining online platforms and examining their current status. It then explores the reasons behind the platform economy’s rise to power and success, comparing and analyzing the development stories and business models of leading online platforms in China and the United States. By examining company profiles, the paper illustrates how these platforms have grown and adapted. The focus then shifts to China’s online platforms, evaluating current policies and the challenges faced by the market and industry. The paper concludes by summarizing the impact of online platforms in both countries and providing forecasts and outlooks based on the collected data. This comprehensive analysis highlights the strategic differences and similarities between Chinese and American online platforms, offering insights into future trends and policy implications. Through this approach, the paper aims to contribute to the understanding of the global platform economy and its role in shaping modern business landscapes. This comprehensive study aims to offer valuable insights into the transformative role of online platforms in the digital economy and guide future research and policy-making in this rapidly evolving field.